Fly Ash – Alginate Composites Beads for Rhodamine B Removal - Heni Anggorowati; Perwitasari Perwitasari; Indriana Lestari (Eksergi, 2022)
Dyes are a very serious problem for the environment. Composite beads consisting of fly ash and sodium alginate proved to be an adsorbent to reduce rhodamine b from dye waste. In this study, the effect of the mass of beads (5-45 grams), the pH of the solution (2-11) and the stirring time (0-360 min) was studied. Determination of concentration after adsorption was carried out by UV-Vis spectrophotometer. The maximum reduction in rhodamine b concentration of 31.15% was obtained after the adsorption process for 300 minutes with a mass of 35 grams of beads. The adsorption of rhodamine b is quite sensitive to the pH of the solution and shows the optimum adsorption value at pH 2. Based on the characterization with BET, fly ash – alginate beads include mesopores with a pore diameter of 10 nm, a total pore volume of 5,332 x 10-3 cc/g and a pore surface area. 2,133 m2/g